Sex differences in arterial hypertension: A scientific statement from the ESC Council on Hypertension, the European Association of Preventive Cardiology, Association of Cardiovascular Nursing and Allied Professions, the ESC Council for Cardiology Practice, and the ESC Working Group on Cardiovascular Pharmacotherapy. (22nd September 2022) - Gerdts, Eva; Sudano, Isabella; Brouwers, Sofie; Borghi, Claudio; Bruno, Rosa Maria; Ceconi, Claudio; Cornelissen, Véronique; Diévart, François; Ferrini, Marc; Kahan, Thomas; Løchen, Maja-Lisa; Maas, Angela H E M; et al.
Graphical Abstract: Graphical Abstract Sex differences in hypertension. BP, blood pressure; CV, cardiovascular; T2D, type 2 diabetes; OSAS, obstructive sleep apnoea syndrome; LVH, left ventricular hypertrophy; LV, left ventricular; LA left atrial; HFpEF, heart failure with preserved ejection fraction; BB, beta blocker; CCB, calcium channel blocker; HFrEF, heart failure with reduced ejection fraction. Abstract: There is strong evidence that sex chromosomes and sex hormones influence blood pressure (BP) regulation, distribution of cardiovascular (CV) risk factors and co-morbidities differentially in females and males with essential arterial hypertension. The risk for CV disease increases at a lower BP level in females than in males, suggesting that sex-specific thresholds for diagnosis of hypertension may be reasonable. However, due to paucity of data, in particularly from specifically designed clinical trials, it is not yet known whether hypertension should be differently managed in females and males, including treatment goals and choice and dosages of antihypertensive drugs. Accordingly, this consensus document was conceived to provide a comprehensive overview of current knowledge on sex differences in essential hypertension including BP development over the life course, development of hypertension, pathophysiologic mechanisms regulating BP, interaction of BP with CV risk factors and co-morbidities, hypertension-mediated organ damage in the heart and the arteries, impact on incident CV disease, and differences in the effect of antihypertensive treatment. The consensus document also highlights areas where focused research is needed to advance sex-specific prevention and management of hypertension.